Hepatitis B in Pregnant Woman Detected by Triple Elimination Screening in Public Health Centre: A Case Report - Adang, Gottfrieda Patiencia Taeng-ob; Lada, Christina Olly; Mari, Maria Kurniawati; Gomangani, Yuli Clementina; Ethelbert, Ryan Arnold (Cendana Medical Journal, 2025)
Introduction: Hepatitis is an inflammation of the liver that can develop into fibrosis (scarring), cirrhosis or liver cancer. As a primary health service facility, the public health centre has an important role in handling Hepatitis B in pregnant women through the Maternal and Child Health program, including triple elimination screening and case management. Case Presentation: A 23-year-old female patient came to the public health centre for routine antenatal care examination (G1P0A0) with a gestational age of 30 weeks and 4 days. The patient had no complaints (asymptomatic), had a normoweight (20,46) body mass index, and had stable vital signs, normal systemic findings on physical examination and obstetric examination. But when a triple elimination examination was carried out by rapid diagnostic test, the result shown a reactive HBsAg. Then the patient was sent to another public health centre for further advance blood test, and the result shown that the woman was positive for hepatitis B with 2.16E08 IU/mL(log 8.33) viral load. The patient are given 1x300 mg Tenofovir disoproxil fumarate (TDF) treatment along with education by the doctor in charge for Hepatitis division to consume the drug until at least during childbirth, continued until 3 (three) month after delivery. Conclusion: Identification of pregnant women with Hepatitis B can be early detected by using the triple elimination rapid test (Hepatitis B, Syphilis, HIV) as a mandatory examination for pregnant women. Clinical symptoms for hepatitis B are vary, ranging from asymptomatic to symptomatic such as nausea, vomiting, headache, and malaise, loss of appetite, darker colour of urine, followed by jaundice that appears after 1–2 weeks. However, Hepatitis B in pregnancy is mostly asymptomatic.